Meningoencephalitis in farmed monosex Nile tilapia (Oreochromis niloticus L.) caused by Streptococcus agalactiae - Adikesavalu Harresh; Banerjee Sayani; Patra Avijit; Abraham Thangapalam Jawahar (Archives of Polish Fisheries, 2017)
Aquaculture of tilapia is a new research venture in India. With intensification in farming practices, tilapia are increasingly susceptible to bacterial infections. This article describes the isolation and identification of pathogenic bacteria from cultured monosex Nile tilapia, Oreochromis niloticus (L.), that experienced moderate to severe mortalities in West Bengal, India between September and August 2014 and histopathological alterations in various organs. Gram-positive diplococci, identified as Streptococcus agalactiae with Streptococcus identification kits and 16S rDNA sequencing analysis, were isolated from the brain, operculum, and kidney. Other bacteria from the kidney were identified as Aeromonas sobria, A. caviae, Klebsiella pneumoniae ssp. pneumoniae, Escherichia coli, and Enterobacter cloacae. Staphylococcus epidermis was isolated from opercular hemorrhages. Histological sections of the infected tilapia brain revealed meningoencephalitis and granulomatous lesions. Sections from other organs indicated congestion, hemorrhagic and hyperplastic cells, necrosis, vacuolation, hemosiderin deposition, hypertrophic nuclei, melanomacrophage aggregation, and ruptured veins. This report is the first description of S. agalactiae as a primary pathogen causing meningoencephalitis in cultured tilapia in India.